(untitled) (Práxis Educativa, 2021)
This article observes the criteria for measuring the Brazilian journals quality according to the parameters established by the Coordination for the Improvement of Higher Education Personnel (CAPES) in the documents referring to Area 38 – Education, of the Technical-Scientific Council of Higher Education and other official agencies. The objective is to understand the indexing growing importance and the use of bibliometric indicators for the classification of journals in stratum A1, highlighting the disputes between actors in the field. The analyzes are theoretically based on the notions of field and scientific capital by Pierre Bourdieu, scientific ethos, imperatives, and Matheus effect, by Robert Merton, as well as on complexity, monoculture, and polyculture, by Leonardo Boff. The results point to the need to rethink protectionist practices, which put the existence of the field at risk, replacing them by engaging in a greater and interdisciplinary dialogue. Keywords: Education. Journal’s evaluation. Disputes between actors.